Impact of an 8-Month Trial Using Height-Adjustable Desks on Children’s Classroom Sitting Patterns and Markers of Cardio-Metabolic and Musculoskeletal Health - Contardo Ayala, Ana María (Int J Environ Res Public Health, 2016)
During school hours, children can sit for prolonged and unbroken periods of time. This study investigated the impact of an 8-month classroom-based intervention focusing on reducing and breaking-up sitting time on children’s cardio-metabolic risk factors (i.e., body mass index, waist circumference, blood pressure) and perceptions of musculoskeletal discomfort. Two Year-6 classes (24 students per class) in one primary school were assigned to either an intervention or control classroom. The intervention classroom was equipped with height-adjustable desks and the teacher was instructed in the delivery of pedagogical strategies to reduce and break-up sitting in class. The control classroom followed standard practice using traditional furniture. At baseline, and after 8-months, time spent sitting, standing, stepping, and sitting-bouts (occasions of continuous sitting) as well as the frequency of sit-to-stand transitions were obtained from activPAL inclinometers and the time spent in light-intensity physical activity was obtained from ActiGraph accelerometers. Demographics and musculoskeletal characteristics were obtained from a self-report survey. Hierarchical linear mixed models found that during class-time, children’s overall time spent sitting in long bouts (>10 min) were lower and the number of sit-to-stand transitions were higher in the intervention group compared to the control group, while no changes were observed for musculoskeletal pain/discomfort. No significant intervention effects were found for the anthropometrics measures and blood pressure. Height-adjustable desks and pedagogical strategies to reduce/break-up sitting can positively modify classroom sitting patterns in children. Longer interventions, larger and varied sample size may be needed to show health impacts; however, these desks did not increase musculoskeletal pain/discomfort.